Research on burr formation mechanism in metal cutting with a backup material. Issue 5 (September 2016) - Zou, Zhijie; Liu, Liangwei; Li, Binglin; Deng, Wenjun
Abstract In order to investigate the mechanism of burr formation and burr minimization, experiment and finite element simulation were performed using identical backup material. The influences of backup material height and thickness on burr sizes and burr profiles were characterized. The experimental results and simulated analyses indicated that effective burr control can be achieved using appropriate selection of backup material parameters. Furthermore, the cutting forces at steady state were found to be the same with different backup material heights and thicknesses. Therefore, the proposed technique will have a wide range of application prospects saving time and cost of deburring. This may bring remarkable economical and societal benefits.